PERAN PEMBIAYAAN MODAL KERJA MURABAHAH DALAM MENDUKUNG PERKEMBANGAN USAHA MIKRO KECIL DAN MENENGAH (UMKM) PADA MASYARAKAT DI KECAMATAN SAMBAS (Studi pada Bank Kalbar Syariah Cabang Sambas) - fitriana; Kusnadi, iwan (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2024)
Islamic Bank is a financial institution that collects public funds in the form of savings and distributes them to the public, in order to improve an economy. Bank financial institutions are very important to help micro, small and medium enterprises (MSMEs) who have difficulties in business capital issues. This research uses a type of descriptive qualitative research, which is obtained from the results of observational data and interviews which are described descriptively. The benefit of this research is to find out whether the role of murabahah working capital financing in supporting the development of a micro, small and medium enterprise has been carried out properly so that an MSME has progressed. The results of this study indicate that the role of murabahah working capital financing provided by Bank Kalbar Syariah Sambas Branch is very influential so that it can have a good impact on the business sector, so that the business being carried out experiences a development, this statement can be strengthened by the smooth payment of installments from business actors and a review of the business location was carried out from the Bank Kalbar Syariah Sambas Branch in the financing sector, and with full support in the form of providing facilities, namely business nameplate banners, table numbers, barcodes, EDC machines provided by Bank Kalbar Syaraiah Sambas Branch for the MSME business sector then the business being carried out is increasingly progressing very rapidly in business development, this is also supported by customers who make financing at the Sambas Branch Sharia Bank Kalbar, explaining that with the murabahah working capital financing the business he is undertaking is developing and experiencing a business progress.